DOI: 10.14264/uql.2016.44
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, engagement, and the evaluation of a parenting intervention for improving sibling relationships

Abstract: Siblings play an integral role in shaping each other's psychosocial development. Sibling relationships marked by positive, prosocial interactions provide an ideal platform for individuals to acquire essential life skills that will benefit them throughout life. On the other hand, early sibling relationships marked by elevated levels of hostility and conflict can have serious long-term, negative consequences. Of all the factors that influence the sibling relationship, few are as important as parents. Currently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 142 publications
(284 reference statements)
0
4
0
Order By: Relevance
“…Studies evaluating MANUSCRIPT ACCEPTED FOR PUBLICATION IN J FAM PSYCHOL 17 Nov 2020 9 mediation came from the same research group (Ross & Lazinski, 2014;Siddiqui & Ross, 2004;Smith & Ross, 2007) and were more similar in terms of intervention characteristics (one or two individual sessions with instructions and role-play) and outcomes (mainly sibling communication techniques), as well as being more prevention oriented, targeting the general population. Studies evaluating behavior management came from different research groups (Adams & Kelley, 1992;Pickering, 2016;Tiedemann & Johnston, 1992;Vickerman, Reed, & Roberts, 1997), varied more in terms of intervention characteristics (one to five sessions, group discussions versus individual sessions with instructions) and outcomes (e.g., sharing versus aggression), and were more treatment oriented, targeting parents concerned about children's interactions (Tiedemann & Johnston, 1992) or with identified interaction problems (Vickerman et al, 1997). The study integrating the two approaches (Linares et al, 2015) adopted yet another approach, with a more intensive intervention in foster families.…”
Section: Narrative Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Studies evaluating MANUSCRIPT ACCEPTED FOR PUBLICATION IN J FAM PSYCHOL 17 Nov 2020 9 mediation came from the same research group (Ross & Lazinski, 2014;Siddiqui & Ross, 2004;Smith & Ross, 2007) and were more similar in terms of intervention characteristics (one or two individual sessions with instructions and role-play) and outcomes (mainly sibling communication techniques), as well as being more prevention oriented, targeting the general population. Studies evaluating behavior management came from different research groups (Adams & Kelley, 1992;Pickering, 2016;Tiedemann & Johnston, 1992;Vickerman, Reed, & Roberts, 1997), varied more in terms of intervention characteristics (one to five sessions, group discussions versus individual sessions with instructions) and outcomes (e.g., sharing versus aggression), and were more treatment oriented, targeting parents concerned about children's interactions (Tiedemann & Johnston, 1992) or with identified interaction problems (Vickerman et al, 1997). The study integrating the two approaches (Linares et al, 2015) adopted yet another approach, with a more intensive intervention in foster families.…”
Section: Narrative Synthesismentioning
confidence: 99%
“…Where percentages of single or divorced parents were reported, the majority of parents was married (e.g., Ross & Lazinski, 2014;Smith & Ross, 2007). One study (Pickering, 2016) reported 8% were step-families. In other words, diversity in family forms was limited, both between and within studies.…”
Section: Narrative Synthesismentioning
confidence: 99%
See 2 more Smart Citations